THE ROLE OF LOCAL SOCIAL INSTITUTION IN COMMUNITY EMPOWERMENT IN BANDUNG REGENCY, INDONESIA - Helly Ocktilia (Indonesian Journal of Social Work, 2019)
This study aims to gain a deeper understanding of the existence of the local social organization in conducting community empowerment. The experiment was conducted at Community Empowerment Institution (In Indonesia it is referred to as Lembaga Pemberdayaan Masyarakat/LPM). LPM Cibeunying as one of the local social institution in Bandung regency. Aspects reviewed in the study include the style of leadership, processes, and stages of community empowerment, as well as the LPM network. The research method used is a case study with the descriptive method and qualitative approach. Data collection was conducted against five informants consisting of the Chairman and LPM’s Board members, village officials, and community leaders. The results show that the dominant leadership style is participative, in addition to that, a supportive leadership style and directive leadership style are also used in certain situations. The empowerment process carried out per the stages of the empowerment process is identifying and assessing the potential of the region, problems, and opportunities-chances; arranging a participative activity plan; implementing the activity plan; and monitoring and evaluating the process and results of activities. The social networking of LPM leads to a social network of power in which LPM can influence the behavior of communities and community institutions in utilizing and managing community empowerment programs. From the research, it can be concluded that the model of community empowerment implemented by LPM Cibeunying Village is enabling, empowering, and protecting.